Analisis Vector Autoregression (VAR) Terhadap Hubungan Antara Luas Panen, Produksi Dan Produktivitas Panen Padi (Studi Kasus Kota Yogyakarta Tahun 1993 -2015) - Muhammad Syahril (Paspalum: Jurnal Ilmiah Pertanian, 2021)
Rice is the staple food of the majority of Indonesian people, including people in the Yogyakarta area, but until now the government still relies on massive, amounts of rice imports from abroad, so that it makes researchers interested in conducting research on Indonesian agricultural productivity which was sampled from the Yogyakarta area as a test material through Central Bureau of Statistics. This study aims to examine whether the harvested area, production level and productivity have a mutually influencing relationship. Researchers used Vector Auto Regression analysis. The results of the study found that the harvested area had an effect on the increase in production value, on the contrary it decreased in productivity, another effect was also found that production on land area and little effect on productivity.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//